Exploring the Contemporary State of Information Technology Governance Transparency in Indonesian Firms - Abdelrahman, Almoazer; Firdausi Nuzula, Nila; Luthfi Imam Fahrudi, Agung Nugroho (Profit: Jurnal Adminsitrasi Bisnis, 2024)
Organizations are placing greater importance on utilizing Information Technology (IT), and efficiently administrating IT resources is crucial for attaining strategic objectives and minimizing IT-related hazards. Nevertheless, there needs to be more comprehension regarding the current status of transparency in IT governance among Indonesian organizations. This study aims to examine the present condition of IT governance disclosure and analyze how the level of IT usage and ownership structure influence the transparency of IT governance in Indonesia. The data collection process will comprise conducting content research on the 2021 annual reports of different organizations using the qualitative analysis approach. This method will investigate high-tier listed corporations, non-listed companies, and low-tier non-listed companies. The study's discoveries will offer significant perspectives for policymakers, managers, and academics, aiding businesses in formulating effective strategies to enhance transparency and IT governance practices. Consequently, this will result in improved organizational performance.